THE EFFECT OF COMPETENCY AND WORK-LIFE BALANCE ON THE PERFORMANCE OF MILLENNIAL GENERATION EMPLOYEES - Rismaja Putra (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
This study aims to analyze the influence of competence and work-life balance on the performance of millennial generation employees, both partially and simultaneously. A quantitative approach with a survey design was used, involving 85 millennial employee respondents (born 1981–1996) selected through purposive sampling. Data were collected using a 1–5 Likert scale questionnaire and analyzed by multiple linear regression using IBM SPSS Statistics 26. The results of the study proved that competence had a positive and significant effect on the performance of millennial employees partially (b₁ = 0.463; t = 6.257; sig. = 0.000), as well as work-life balance (b₂ = 0.312; t = 4.952; sig. = 0.000). Simultaneously, both variables had a significant effect on performance (F = 48.217; sig. = 0.000) with an explanatory power of 53.9% (R² = 0.539). Competence contributes more to performance than work-life balance, indicating that investing in millennial employee competency development is a top strategic priority. This study is the first to simultaneously integrate both variables with generation-specific millennial subjects, filling a gap in previous research.